To get the best deal on Tutoring, call 1-855-666-7440 (Toll Free) Top

Quadratic equation is the polynomial equation of degree "two" in one variable. More precisely, we can say that an equation of the form is known as quadratic equation.
a, b and c are constants and x is the variable.
"a" must not be zero because if "a" equals zero, the equation will be no more an equation of degree two.

Quadratic equations can be solved by various methods. By solving a quadratic equation, we mean finding the value of variable contained in it.

Methods for Solving Quadratic Equations

(1) Factorization:
To solve a quadratic equation $ax^{2}+bx+c=0$ by this method, we follow the following steps:
• Determine the value of a, b and c.
• Calculate the product a*c.
• Split the value of "b" in two parts so that their sum or difference is equal to "b" and product is equal to "ac".
• Substitute the split parts in place of b.
• Separate like terms and take common factors out.
For Example: $3x^{2}+2x-1=0$
a = 3, b = 2, c = -1
a * c = -3 = 3 * (-1)
b = 2 = 3 - 1
$3x^{2}+(3 - 1)x-1=0$
$3x^{2}+3x-x-1=0$
3x (x + 1) - 1(x + 1) = 0
(x + 1) (3x - 1) = 0
x = -1, $\frac{1}{3}$

(2) Completing the Square:
Quadratic equations can be solved by completing the perfect square and using the suitable identities.
For example: $x^{2}+4x+1=0$
$x^{2}+4x+4-4+1=0$
$(x^{2}+4x+4)-4+1=0$  (we know that $(a+b)^{2}=a^{2}+2ab+b^{2}$)
$(x+2)^{2}-3=0$
$(x+2)^{2}-(\sqrt{3})^{2}=0$
$(x+2+\sqrt{3})(x+2-\sqrt{3})=0$  (we have $a^{2}-b^{2}=(a+b)(a-b)$)
$x = -2+\sqrt{3}$
$x = -2-\sqrt{3}$

(3) Quadratic Formula: We can use the following quadratic formula to find the solution of a quadratic equation - For Example: $x^{2}+x-1=0$
Here, a = 1, b = 1, c = -1

$x=$$\frac{-b\pm \sqrt{b^{2}-4ac}}{2a} x=$$\frac{-1\pm \sqrt{1+4}}{2}$

$x=$$\frac{-1\pm \sqrt{5}}{2} => x=$$\frac{-1+ \sqrt{5}}{2}$ and $x=$$\frac{-1- \sqrt{5}}{2}$

 Related Calculators C Quadratic Equation Solver Factor Quadratic Equation Calculator Graphing Quadratic Equations Calculator

 More topics in  Quadratic Equations Factoring Quadratic Equations Graphing Quadratic Functions Graphing Quadratic Equations How to Solve Quadratic Equations by Graphing
*AP and SAT are registered trademarks of the College Board.